Optimalisasi Pengendalian Persediaan Biji Kopi Dengan Metode EOQ (Studi Kasus Kopi Bubuk Eyang Kakung) - Satria Bayu Nugraha; Moh. Jufriyanto; Ahmad Wasiur Rizqi (Fakultas Teknik, 2023)
Kopi Bubuk Eyang Kakung is one of the micros, small and medium enterprises (MSMEs) in Gresik which operates in the field of coffee bean processing. This company often faces a situation where raw material supplies are close to running out, which is often referred to as stockout. To solve these challenges related to inventory management, Kopi Bubuk Eyang Kakung tries to use the economic order quantity (EOQ) methodology. EOQ is an important technique in procuring raw materials in a company, which aims to determine the most economical order quantity for each purchasing cycle, while determining the order frequency and optimal time for reordering. The use of the EOQ method is helpful in reducing costs associated with inventory, thereby ensuring effective operation of the inventory system. This method facilitates achieving optimal order quantities while minimizing costs. Specifically, the EOQ method determines the most efficient order quantity by considering the costs per period related to raw materials for BM coffee beans of IDR 140,724, JM of IDR 213,065, and BA of IDR 88,228.